2018
DOI: 10.3389/fpsyg.2018.01458
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Veterans With PTSD: Comparison Between Intensive Daily and Weekly EMDR Approaches

Abstract: The effectiveness of EMDR therapy in treating veterans diagnosed with PTSD was evaluated in this study using two treatment formats: intensive daily EMDR treatment provided twice a day during a 10-day period and a second format of one session each week. The study used archived outcome data previously collected and stored at Soldier Center. Both formats provided 18–20 treatment sessions of EMDR therapy to veterans diagnosed with PTSD that included dissociative exhibitions and moral injury issues. Questions addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
2
22
0
5
Order By: Relevance
“…The results of the random-effects modeling revealed a mean Cohen's d effect size 1.57, 95% CI [1.24, 1.91], which denotes a large impact of treatment on symptom reduction. Moreover, the findings from studies in which long-term follow-up assessments were conducted found that intensive treatments were associated with large improvements in PTSD symptoms at varying posttreatment intervals (Bryan et al, 2018;Ehlers et al, 2010Ehlers et al, , 2014Foa et al, 2018;Hendriks et al, 2018;Hurley, 2018;Van Woudenberg et al, 2018), Cohen's ds = 0.74-2.59.…”
Section: Symptom Ameliorationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the random-effects modeling revealed a mean Cohen's d effect size 1.57, 95% CI [1.24, 1.91], which denotes a large impact of treatment on symptom reduction. Moreover, the findings from studies in which long-term follow-up assessments were conducted found that intensive treatments were associated with large improvements in PTSD symptoms at varying posttreatment intervals (Bryan et al, 2018;Ehlers et al, 2010Ehlers et al, , 2014Foa et al, 2018;Hendriks et al, 2018;Hurley, 2018;Van Woudenberg et al, 2018), Cohen's ds = 0.74-2.59.…”
Section: Symptom Ameliorationmentioning
confidence: 99%
“…These five studies varied in study design, population, location of services, and EST. Despite this variability, all studies with an available comparison group reported a lower or similar dropout rate from the intensive condition compared with the standard treatment condition (Ehlers et al, 2014;Foa et al, 2018;Hurley, 2018). Of note, the study that reported the highest dropout rate (n = 15, 13.6%) from an intensive treatment condition (i.e., daily PE; Foa et al, 2018) included participants who never initiated treatment; of the participants who initiated therapy, 3.6% (n = 4) did not complete treatment.…”
Section: Treatment Dropoutmentioning
confidence: 99%
“…Similar to the multitude of moral injury measures, we noted there are a plethora of treatments currently available for moral injury. Dr. Gray presented on Adaptive Disclosure, but other proposed treatment options include Prolonged Exposure (Foa et al, 2007), Cognitive Processing Therapy (Resick et al, 2017), Spiritually Integrated Cognitive Processing Therapy (Pearce et al, 2018), Impact of Killing (Maguen et al, 2017), Acceptance and Commitment Therapy (Nieuwsma et al, 2015), and Eye Movement Desensitization and Reprocessing therapy (Hurley, 2018). Yet, despite the impressive number of intervention options, there is a general lack of efficacy or effectiveness data supporting their utility for treating moral injury (Griffin et al, 2019).…”
Section: Applicationsmentioning
confidence: 99%
“…In this study, intensive EMDR therapy was provided [93][94]. Evidence suggests that more frequent scheduling of treatment sessions maximized PTSD treatment outcomes [95].…”
Section: Treatmentmentioning
confidence: 98%